IGBT-SiC dual fed open end winding PMSM drive - Rovere, Luca; Formentini, Andrea; Lo Calzo, Giovanni; Cox, Tom; Zanchetta, Pericle (2017)
This paper proposes a dual fed common dc link inverter Open End Winding-Permanent Magnet Synchronous Motor (OEW-PMSM) Drive. In order to increase the system efficiency a dual technology converter is used, with one inverter composed of standard IGBT devices and the other composed of fast switching Silicon Carbide (SiC) devices. The common dc link OEW configuration allows the zero-sequence current (ZSC) to flow freely, and the low time constants of the zero-circuit can lead to high zero sequence current flow, with associated losses and stress on the power devices. To avoid this, the zero-sequence voltage produced by the switching combinations adopted to synthetize the control signals needs to be instantaneously eliminated. A novel modulation for dual converter configurations is proposed to eliminate the zero-sequence voltage(ZSV).